Child Trafficking and Associated Factors in Earthquake Affected Area of Nepal - Baniya, Ambika; Chhetri, Mamta; Paudel, Ashok Kumar; Thapa, Rasmi; Adhikari, Rita (Journal of Karnali Academy of Health Sciences, 2020)
Background: Child trafficking popularly known as recruitment, transportation, transfer, harboring, and/or receipt of kidnapping of under 18 years child. The purpose of trafficking might be for forced labor, slavery and different types of exploitation including sexual exploitation. The main objective of this study was to assess the knowledge about child trafficking and factors associated with child trafficking in Gorkha district of Nepal Methods: Cross sectional study conducted to determine the knowledge and factors related to child trafficking in Gorkha district. Two urban municipalities selected purposively and other three rural municipalities were randomly selected. Out of 160,772 households, total 300 households for survey was calculated by using Yamane formula (n) = N/ (1+Ne2). Wards of the municipalities were Primary Sampling Unit. Based on Population Proportionate Sampling technique; required number of households of each Wards was identified. In Wards, households for survey were selected by using simple random method. Head of the selected household were the respondent for household survey. Ten Key Informant Interviews were done with policemen, teachers, social workers, community leaders, stakeholders and six Focus Group Discussions were done with Youths (15-25 years), Parents and Social worker/teacher/community leader groups. Results: Remarkable proportions of respondents have correct knowledge about the child trafficking. Near relatives, unknown person, pears group, parents/family members and neighbor were common traffickers. During and after disaster is the most vulnerable time/event for child trafficking. False marriage, assuring lucrative job, asking for adoption and proposing good education were tricks of traffickers for child trafficking. Homeless children, children travelling without parents, socially isolated children, children travelling at night, unprotected girl, orphan children separated from family or without parent are most vulnerable for child Trafficking. Conclusion: Family, social groups, government officials and stakeholders should jointly initiate for anti- child trafficking movement. School teacher and management committee should also take initiation to make fully aware to school going children about different dimensions/aspects of Child Right and Child Trafficking.